City of bones - Clare, Cassandra (New York : Margaret K. McElderry Books, 2007)
Suddenly able to see demons and the Darkhunters who are dedicated to returning them to their own dimension, fifteen-year-old Clary Fray is drawn into this bizzare world when her mother disappears and Clary herself is almost killed by a monster.
Ages 14 up.
Keywords: Demonology -- Juvenile fiction; Occult fiction; Magic -- Juvenile fiction; Horror tales; Fantasy fiction